Fantasia (Unforgettable Dream) / Mohammad Harris M. Yahya ... [et al.] - M. Yahya, Mohammad Harris; Abdul Wahab, Hasrul; Mohd Nadzin, Mohd Safuan; Sabrom, Noor Hidayah; Saidi, Fadhilah (Faculty of Applied Sciences, 2005)
We have agreed to choose Fantasia (Unforgettable Dream) as the name of our business. Fantasia (Unforgettable Dream) means our businesses innovation inline with an up to date bedroom bridge design. We think that the mention name is suitable for our goals as well as to give the spirit running the business.